A Multigroup, Longitudinal Study of Truant Youths, Marijuana Use, Depression, and STD-Associated Sexual Risk Behavior. Issue 3 (4th May 2017) - Dembo, Richard; M. Krupa, Julie; Wareham, Jennifer; Schmeidler, James; DiClemente, Ralph J.
ABSTRACT: Truant youths are likely to engage in a number of problem behaviors, including sexual risky behaviors. Previous research involving non-truant youths has found sexual risk behaviors to be related to marijuana use and depression, with differential effects for male and female youths. Using data collected in a National Institute on Drug Abuse (NIDA)-funded, prospective intervention project, results are reported of a male-female, multi-group, longitudinal analysis of the relationships among truant youth baseline sexual risk behavior, marijuana use, and depression, and their sexual risk behavior over four follow-up time points. Results indicated support for the longitudinal model, with female truants having higher depression scores, and showing stronger relationships between baseline depression and future engagement in sexual risk behavior, than male truants. Findings suggest that incorporating strategies to reduce depression and marijuana use may decrease youth sexual risk behavior.